(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The intensification of the concerns about the co-production process is due to the awareness of its importance as a phenomenon. The attention of the scientific community, those involved in economics, management or marketing, as well as psychologists, has turned over the past decades into the coproduction phenomenon. They considered the aspect of co-production between companies that put together resources to achieve a common goal, but especially the aspect of co-production between the producer of goods and services, on the one hand, and their beneficiary, on the other. The emergence of the new producer, which allows the beneficiary to co-produce with him and the new informed consumer, eager for innovation, emotion, experience, illustrates these changes. In our view, coproduction theory provides useful information about the quality of collaborative work, which inspires the mechanisms necessary to generate the new product, the importance of each party’s involvement in the coproduction process, the importance of emotional satisfaction in determining the improvement of results. Sample research had as a general objective the deepening, from the point of view of the respondents - with conceptual conclusions - of the coproduction between the bidder and the beneficiary in the educational process, in light of several elements through which the co-production can be reflected, namely: co-involvement, co-planning, co-administration of time, co-learning / intelectual co-training, co-evaluation and inter-adaptability of the bidder and beneficiary. In this article I took into consideration the relationship between co-production and co-planning, on the one hand, and between co-production and the offerer’s attitude as a trigger or inhibitor, on the other.